Teatrul spontaneității - Beca, Elena (Calitatea Vieții, 1993)
The theater of spontaneity is the place where the human community is testing the reality of their own lifes. It is a post-cartesian "knowing yourself" within the spirit of the XX century. Confirming the individuality through imparting experience within the group, the theater of spontaneity contributes at the building of the individual from the exterior to interior, the group becoming the garrant in defining reality.